Outcome in 12 Dogs with Chronic Radiographic Cranial Tibial Subluxation after Tibial Plateau Leveling Osteotomy (2019-2021) - Jacqueline M. Harrison; Peter Muir (Case Reports in Veterinary Medicine)
Objective. The objective of this study was to examine outcomes in dogs with cruciate ligament rupture (CR) that had chronic radiographic cranial tibial subluxation at the time of osteotomy healing after tibial plateau leveling osteotomy (TPLO). Study Design. Retrospective case analysis of 12 dogs with prospective follow-up. Four of the 12 dogs were prospectively studied 12-24 months after surgery to assess long-term radiographic and clinical outcomes. Results. Three of the 4 dogs showed improvement in radiographic cranial tibial subluxation at long-term follow-up. In the other dog, minimally improved cranial tibial subluxation was associated with severe lameness. At long-term follow-up, gait analysis in 3 dogs with improved subluxation showed the symmetry of weight-bearing within 10% for peak vertical force, and no clinically lameness. Preoperative tibial plateau angle (TPA) and radiographic osteoarthritis in dogs with prospective follow-up and all dogs treated with TPLO surgery in the study period were not significantly different. Conclusion. Dogs with chronic radiographic cranial tibial subluxation are acceptable candidates for TPLO. Radiographic improvement in stifle reduction may take more than 10 weeks. The dog with long-term persistent subluxation also had a higher TPA over time, suggestive of ineffective surgical correction with TPLO and treatment failure.